Alternative Fates of Keratinocytes Transduced by Human Papillomavirus Type 18 E7 during Squamous Differentiation - Chien, Wei-Ming (American Society for Microbiology, 2002)
The human papillomavirus type 18 (HPV-18) E7 protein promotes S-phase reentry in postmitotic, differentiated keratinocytes in squamous epithelium to facilitate vegetative viral DNA amplification. To examine the nature and fate of the differentiated cells that reenter S phase, organotypic cultures of primary human keratinocytes transduced with HPV-18 E7 were pulse-chase-pulse-labeled with (3)H-thymidine ((3)H-TdR) and bromodeoxyuridine (BrdU). The kinetics of the appearance of doubly labeled suprabasal cells demonstrate that E7 expression did not promote prolonged S phase. Rather, there was a considerable lag before a small percentage of the cells reentered another round of S phase. Fluorescence in situ hybridization analysis, indeed, revealed a small fraction of the cells with more than 4n chromosomes in the differentiated strata. Differentiated cells positive for (3)H-TdR, BrdU, or both often had enlarged nuclei or were binucleated. These results suggest that S phase is not followed by cell division, although nuclear division may occur. Interestingly, a significant fraction of differentiated cells that entered S phase subsequently accumulated p27kip1 protein with a kinetics preceding the accumulation of cyclin E. We conclude that E7-transduced, differentiated keratinocytes that enter S phase have two alternative fates: (i) a low percentage of cells undergoes endoreduplication, achieving higher than 4n ploidy, and (ii) a high percentage of cells accumulates the p27kip1, cyclin E, and p21cip1 proteins, resulting in arrest and preventing further S-phase reentry.